2017
DOI: 10.1002/ijgo.12213
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of thrombophilia in patients with unexplained recurrent pregnancy loss using a statistical model

Abstract: The LRM is a valuable model for prediction of thrombophilia in URPL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…All women enrolled underwent an extensive screening as described in a previous study to elucidate all known potential etiologies of RPL. 19 Patients with a history of at least three consecutive first-trimester pregnancy losses with unexplained etiology (i.e. negative for uterine anatomic abnormalities, negative for genetic anomalies, negative for autoimmune diseases) were included in the URPL group.…”
Section: Materialsandmethodsmentioning
confidence: 99%
“…All women enrolled underwent an extensive screening as described in a previous study to elucidate all known potential etiologies of RPL. 19 Patients with a history of at least three consecutive first-trimester pregnancy losses with unexplained etiology (i.e. negative for uterine anatomic abnormalities, negative for genetic anomalies, negative for autoimmune diseases) were included in the URPL group.…”
Section: Materialsandmethodsmentioning
confidence: 99%
“…TAFI is essential for the precise regulation of the local coagulation–fibrinolysis system. 5 , 18 ElDanasori et al 18 investigated the TAFI function in early pregnancy population and found that in addition to regulating the balance of coagulation–fibrinolysis during pregnancy, the high concentration level of TAFI in the low fibrinolytic state could inhibit the formation of fibrin degradation products, reduce the apoptosis of placental trophoblast cells, and was beneficial to normal pregnancy. RSA can be caused by genetic polymorphisms in the maternal hemostatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Precise regulation of the coagulation–fibrinolysis system under normal physiological hypercoagulability plays an important role in embryo implantation and trophoblastic invasion, and abnormal coagulation mechanisms may be a risk factor in women with RSA. 5 Thrombin-activatable fibrinolysis inhibitor (TAFI), also known as procarboxypeptidase U, plasma procarboxypeptidase B, or procarboxypeptidase R, is a procarboxypeptidase that is mainly synthesized by the liver and exists as an inactive zymogen in the blood circulation. TAFI can be activated by thrombin, thrombin–thrombin regulatory protein, and plasmin, and regulates early trophoblast cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the RPL group were grouped according to the number of spontaneous abortion times. All patients enrolled underwent comprehensive examinations by using currently existing methods to evaluate all known etiologies of RPL, in accordance with the previously described diagnostic flow chart . Patients were subsequently grouped according to the different etiologies of RPL.…”
Section: Methodsmentioning
confidence: 99%